Of Gongs and Cannons: Music and Power in Island Southeast Asia - Jeremy Wallach (Wacana Seni Journal of Arts Discourse, 2004)
This essay engages with a miscellaneous assortment of writings which span over four and a half centuries. Most of these texts have something to do with Island Southeast Asia, particularly the area formerly known as the Dutch East Indies (Indonesia), and with the exploration, colonization, and domination of this region by Europeans from the sixteenth century to the present. This project therefore falls under the general rubric of postcolonial studies, and I hope to make a positive contribution to that field by attempting to destabilize conventional scholarly views on music and power, and the roles these play in the discourses of postcolonial musicology and ethnomusicology.